An in-silico approach to evaluate bioactive molecules of aloe vera leaf extracts in inhibiting the glycogen synthase kinase-3β (GSK3-β) protein for faster diabetic wound healing potential - Roney, Miah; Mohd Fadhlizil Fasihi, Mohd Aluwi; Normaiza, Zamri (Biointerface Research, 2024)
A complex web of dynamic systems is involved in the wound healing of excisional skin injuries, which poses a significant therapeutic challenge. Skin graft transplantation and wound dressings are among the several methods that have been suggested in order to preserve the essential structure and function of the damaged tissue. GSK3-β, which is a main target to accelerate the healing process of wounds, is a signaling route that is part of the PI3K/AKT pathway, which is activated phosphatidylinositol 3 kinase/protein kinase B pathway. The efficient use of natural products in wound care has been the subject of extensive research in recent years. Natural products offer a multi-targeted strategy, particularly in treating chronic wounds, because they include many phytoconstituents that may work on different phases of wound healing. The effectiveness of the main compounds found in aloe vera leaf extracts as wound-healing agents against GSK3-β was evaluated in this work using in-silico techniques. Compared to the co-crystallized ligand (-6.2 kcal/mol), aloenin 2'-p-coumaroyl ester showed high docking scores (-9.5 kcal/mol) and robust binding to the GSK3-β protein. The docking properties of Aloenin 2'-p-coumaroyl ester and the outcomes of molecular QSAR might be further utilized to develop a GSK3-β inhibitor.